BODY SHAMING BEHAVIOR REPRESENTATION AGAINST RARA CHARACTERS IN THE MOVIE ‘IMPERFECT’ (JOHN SEMIOTICS ANALYSIS FISKE) - Rifqi Ramdani Fawzi; Rizca Haqqu (Universitas Negeri makassar, 2021)
Bullying is one of a serious issue that happened among societies. Bullying is an act of aggression that is carried out by a group of people or someone intentionally and repeatedly, against someone who is considered weak or as misuse of an organized power or force. Somehow in life, many people didn’t realize that they have verbally bullied others. Most of verbal bullying that people did are mocking, reproach, and ridicule someone's physical or as known as body shaming. Based on the explanation, the researcher is interested to analyze body shaming behavior directed to Rara in the Imperfect movie. In the current phenomenon, researcher think that the people need to pay attention to their behavior who unconsciously do the body shaming. This research use a qualitative method using semiotic analysis to analyze the object under research. By using John Fiske's semiotic analysis, researcher can analyze the object under research using three levels of television from John Fiske, those are level of reality, level of representation, and level of ideology. From the results of this study, it can be said that the Imperfect movie shows act of body shaming behavior towards the character, Rara, which encoded in level of reality, level of representation, and level of ideology